Simultaneous elliptically and radially polarized THz from one-color laser-induced plasma filament. (17th June 2021) - Mou, Sen; D'Arco, Annalisa; Tomarchio, Luca; Di Fabrizio, Marta; Curcio, Alessandro; Lupi, Stefano; Petrarca, Massimo
Abstract: THz-based technologies and research applications have seen a rapid increment in recent period together with the development of novel radiation sources based both on relativistic electrons and laser techniques. In this framework, laser-induced plasma filament plays an important role in generating intense and broadband THz radiation. Although many attentions have been paid to THz emission from two-color plasma filaments, one-color plasma emission has been scarcely investigated. In particular, the polarization state of one-color THz emission is still controversial due to the limitations of the existing THz detection techniques, which are incapable of simultaneously detecting elliptically and radially polarized THz radiation. In this manuscript, we develop a novel detection method and unambiguously demonstrate for the first time that one-color laser-induced plasma filament simultaneously emits elliptically and radially polarized THz radiation. These polarization states suggest that the generation mechanism results from electric quadrupole, showing a new route for producing more complex polarization states and THz vortex beams.